COVID-19 Testing: A Qualitative Study Exploring Enablers and Barriers in the Greater Accra Region, Ghana - Ha, Solip; Yangchen, Sonam; Assan, Abraham (Frontiers in Public Health, 2022)
Introduction The COVID-19 pandemic is a global crisis and has reaffirmed that extensive testing along with effective tracing is still crucial to slowing transmission of the COVID-19 virus despite the rolling out of vaccines. This study explored enablers and barriers to COVID-19 testing in the Greater Accra region of Ghana. We envision lessons learned from this study could serve as a road map to strengthen the current response to COVID-19 and preparedness for future outbreaks, particularly in low- and middle-income countries. Methods A qualitative design was undertaken to explore the phenomenon. Data collection methods included in-depth interviews with key informants with a purposively selected sample of 20 participants. Interviews were conducted using flexible semi-structured interview guides. Depending on the participant's position and involvement in COVID-19 testing, the guides were modified, and key elements were drawn from a tailored version of the WHO Health System Framework, incorporating the Essential Public Health Functions (EPHF). The interview findings were augmented by reviewing published literature. Results Better health governance through political leadership, community participation, multisectoral collaboration, effective resource management, and information systems played a crucial role in catalyzing COVID-19 testing. The primary barriers to testing were mainly COVID-19 infodemic, inadequacy of material resources to meet growing health needs, and a lack of opportunities to have equal and easy access to testing services. Furthermore, although human resources were adequate, they were unevenly distributed across settings. Conclusion Despite rolling out vaccines against COVID-19, testing remains an important measure to control the virus. To effectively be prepared for extensive COVID-19 testing and respond to future outbreaks, the following are recommended: there should be improved political commitments, coordination, and communication with diverse actors to ensure even distribution of all resources across the country; empowerment of community members should be encouraged to develop community-oriented pandemic preparedness and management of COVID-19 infodemic; investment in strengthening capacity of Good Manufacturing Practice (GMP); incorporation of health policy and systems research (HPSR) into the post-COVID-19 pandemic recovery process and future pandemic preparedness.